Highly efficient dual-grating 3-channel spectral beam combining of narrow-linewidth monolithic cw Yb-doped fiber amplifiers up to 5.5 kW - Strecker, Maximilian; Ploetner, Marco; Stutzki, Fabian; Walbaum, Till; Ehrhardt, Sascha; Benkenstein, Tino; Zeitner, Uwe; Schreiber, Thomas; Eberhardt, Ramona; Tunnermann, Andreas; Stuhr, Uwe; Jung, Markus; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
We present highly efficient three-channel dual-grating spectral beam combining with a combined signal output power of 5.5 kW at an excellent beam quality of M2 = 1.5. Three 2-kW all-fiber narrow-linewidth continuous-wave Ytterbium-doped fiber amplifiers at 1050 nm, 1070 nm and 1090 nm were combined using in-house fabricated polarizationindependent dielectric reflection gratings. The total combining efficiency was 94% at full power level, which is close to the expected value referred to the incorporated grating's efficiency in a dual-grating setup.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dielectric reflection grating; Dual-grating setup; Fiber amplifier; Monolithic; Spectral beam combining (SBC)